2021
DOI: 10.1111/avj.13106
|View full text |Cite
|
Sign up to set email alerts
|

Is transportation a risk factor for African swine fever transmission in Australia: a review

Abstract: African swine fever (ASF) is a viral disease of the pigs that was first described in Africa during the early part of the twentieth century. The disease has periodically occurred outside of Africa, including an ongoing epidemic in Europe and Asia that started in 2007; the disease has never occurred in Australia or New Zealand. Once introduced into a country, spread can occur through direct and indirect routes of transmission. Infected feral pig populations have the potential to act as a long‐term reservoir for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 52 publications
1
15
0
3
Order By: Relevance
“…The harbor is also a strategic site for the transportation, buying, and selling of domestic pigs. Although contaminated transport trucks are a risk factor and a source of ASF transmission between farms, reports are not well documented [23]. In contrast, one of the causes of the spread of ASFV is food waste which is used by farmers as a swill for feeding pigs [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The harbor is also a strategic site for the transportation, buying, and selling of domestic pigs. Although contaminated transport trucks are a risk factor and a source of ASF transmission between farms, reports are not well documented [23]. In contrast, one of the causes of the spread of ASFV is food waste which is used by farmers as a swill for feeding pigs [1].…”
Section: Discussionmentioning
confidence: 99%
“…The ASF prevention strategies applied in these examples are strict biosecurity measures on farms which increase the capacity of veterinary services to detect disease, to perform diagnosis, surveillance, management, and emergency and contingency response and care; thus strengthening the capacity of farmers to raise healthy pigs by increasing access to information and training. These programs also limit transportation in order to limit the trade movement of pork, pork products, and related human activities [23,32,33]. Indonesia's geographical environment conditions and characteristics are different from other countries.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of introduction of ASF into Spain via the legal import of live pigs was significantly low (1.07 × 10 −4 ), despite the fact that the import of live animals and their products is considered one of the most important risk factors for the introduction of ASF into an ASF-free country [6][7][8][9]. This seems to indicate that further analyses of other entry pathways, such as the importation of pig meat and biological products (semen, ova, and embryos), should also be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Although the disease has several transmission paths, one of the most important factors for this widespread diffusion across great distances is the vast amount of international trade of live swine and their products [6]. The import of live animals, specifically trucks returning from infected to uninfected areas, is considered one of the most important risk factors for the introduction of contagious animal diseases into an ASF-free country [7,8]. Indeed, authors concluded that the risk of ASF introduction into the EU was mainly associated with returning trucks that were not properly disinfected [9].…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian yang telah dilakukan di Eropa mengenai ASF pada babi hutan diketahui bahwa lingkungan seperti iklim, tutupan lahan, dan keberadaan babi hutan sangat berhubungan dengan kejadian ASF (Bergmann et al, 2021). Selain itu, kontaminasi ASF dapat bersumber dari lantai, peralatan, dan kendaraan (Neumann et al, 2021).…”
Section: Arah Sebaran Kasus Asfunclassified